Geophysical surveys in the Portuguese sector of the Iberian Pyrite Belt: a global overview focused on the massive sulphide exploration and geologic interpretation - Matos, João Xavier (2022)
ABSTRACT: The application of geophysical techniques to massive sulphide deposits exploration has proven to be a success in the Iberian Pyrite Belt (IPB) metallogenetic province, both in Portugal and in Spain. Several hidden deposits were discovered through the interpretation of geological models, supported by geophysical data collected in land and airborne surveys, as well as applied using down hole techniques in selected drill holes. This paper presents an overview of the methodologies applied in Portugal in the South Portuguese Zone (SPZ) geological domain, where the IPB is included, mostly by the LNEG and mining companies, with emphasis on the interpretation of the regional gravity, magnetometry and radiometry surveys, published in 1/400 000 scale by the EXPLORA/Alentejo2020 Project. In this regional mapping program, the large volume of data collected by LNEG and mining companies since the 1960’s was compiled and processed. The integrated interpretation and correlation between these methods will enable a better planning of new IPB exploration investments. IPB Volcano-Sedimentary Complex (VSC, Famennian to Late Visean age) lineaments are well defined in the gravity and magnetic fields along the IPB western region (e.g. Alcoutim/Neves Corvo/Montinho/Sesmarias/Lousal/Caveira). Aeromagnetic data also reflect deep and large anomalies related with the SPZ basement. A rock density database is presented and used to interpret the gravity data. Radiometric map (Natural Radioactivity), based mostly in airborne radiometric surveys, show contrasts between rocks in Paleozoic, Mesozoic and Cenozoic formations and correlations with geological and hydrothermal mapping are highlighted. The use of geophysical techniques is particularly critical in areas where VSC is concealed by younger sediments (e.g. Baixo Alentejo Flysch Group and/or Cenozoic formations), allowing the selection of target areas. Case studies are discussed based on electromagnetic, seismic and magnetotelluric methods and on the high mineral potential of defined targets. Multilayered data correlation (geophysics including petrophysical data, geochemistry and stratigraphic high-resolution models) is a key prospecting methodology and is essential for the accurate modelling of ore horizons and geological structures. Considering the IPB potential for VMS deposits, including the possible discovery of new giant (> 200 Mt) deposits, an increase of investment in new geophysical methods can be predicted. LNEG development of R&D projects such as EXPLORA/Alentejo2020 and SmartExplorationTM/H2020 also contribute to a favourable setting in the province, both in near mining and green fields scenarios. Thus, new discoveries are expected, like others made in the recent times in the IPB Portuguese sector, such as Lagoa Salgada (SFM, 1992, SFM; Redcorp/EDM, 2011; Redcorp/Ascendant/EDM, 2017), Semblana (Somincor-AGC-Lundin Mining, 2010), Monte Branco (Somincor Lundin Mining, 2012) and Sesmarias (Maepa/Avrupa, 2014). The importance of these data goes beyond the mineral exploration purpose. Since some of them use rock and mineral physical properties that can be related with environmental contamination (e.g. radiometry and magnetics) they can also be used in geochemical background studies, acid mine drainage and metal dispersion. Therefore, they can also promote a deeper knowledge in other areas of research related with environment preservation.